Multicultural Values in the Indonesian EFL Textbook 'English for Nusantara’: A critical discourse analysis - Ningtiyas, Ailia Ayu Kusuma; Ghozali, Imam; Nugraheni, Dyah Ayu (Journal of English in Academic and Professional Communication, 2025)
This study examines how multicultural values are portrayed in an English as a Foreign Language (EFL) textbook used in Indonesian middle schools (SMP/MTS) for seventh-grade students. The research utilizes a critical discourse analysis to portray multiculturalism values, including race/ethnicity, gender, social class, and people with disabilities. The data were collected visually and textually through Language Visual Grammar Theory and Appraisal Theory respectively. The analysis shows how these four aspects of multiculturalism are woven into contemporary topics through both visual and textual representations. The findings reveal that the EFL textbook successfully incorporates all four multicultural values, yet the visual and the textual representations are imbalanced. The study concludes that EFL textbooks that present multicultural content according to these parameters serve a vital function in developing students' inclusive mindsets toward cultural differences and fostering appreciation for Indonesia's cultural diversity. The research also suggests that EFL textbooks would benefit from including more international multicultural content, as exposing students to diverse global cultures and perspectives can enhance their worldview and cross-cultural understanding.